Single crystal metal foil and preparation method thereof
By depositing atoms of chalcogenic elements on the surface of the polycrystalline metal foil raw material, the problem of high cost and low efficiency of single crystal metal foil preparation in the prior art is solved, and high single crystal conversion, low energy consumption and low cost preparation is achieved Method, suitable for single crystal metal foils of various two-dimensional sizes.
Patent Information
- Application Number
- CN202411719842.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art has high cost, low efficiency when preparing single crystal metal foils, and the single crystal conversion rate is not high. Due to the size of the metal material, it is difficult to adapt to various two-dimensional sizes.
Before annealing treatment, the polycrystalline metal foil raw material is pretreated, and by co-heat treatment with the substance containing chalcogen elements, the atoms of the chalcogen element are deposited on the surface of the polycrystalline metal foil, thereby improving the single crystal conversion rate.
It significantly improves the single crystal conversion rate and is suitable for the preparation of single crystal metal foils of various two-dimensional sizes, reduces energy consumption and costs, and realizes efficient and low-cost preparation of single crystal metal foils.
Smart Images

Figure CN119433397A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application belong to the field of single crystal material preparation, and in particular, relate to a single crystal metal foil and a preparation method thereof. Background Art
[0002] Single crystal metal foil has broad application prospects in the fields of power transmission and new electronic devices due to its own characteristics of no grain boundaries. At present, the main processes for preparing single crystal metal foil include "stress annealing method" in addition to pure "heat treatment method", that is, applying stress to polycrystalline metal foil during high temperature annealing to obtain single crystals, and "inclined placement annealing method" and "vertical placement annealing method" to promote the formation of single crystals by adjusting the placement of polycrystalline metal foil. However, measures such as applying stress and adjusting the placement method only play a weak auxiliary role, and high temperature annealing is mainly required to achieve the single crystal conversion of polycrystalline metals, which not only consumes a lot of energy and heat, but also cannot avoid the loss of metal materials. Its single crystal conversion rate is also limited by the size of the metal material, resulting in high cost but low efficiency in preparing single crystal metal foil. Therefore, it is necessary to provide a preparation method for single crystal metal foil with high single crystal conversion rate, universal applicability to various two-dimensional sizes, low cost and low energy consumption. Summary of the invention
[0003] In view of this, the present application provides a single crystal metal foil and a preparation method thereof. The preparation method pretreats the polycrystalline metal foil raw material before annealing so that it is heated and fully contacted with a substance containing chalcogen elements and atoms of chalcogen elements are deposited on the surface. The pretreatment can greatly improve the single crystal conversion degree of the polycrystalline metal foil in the subsequent annealing process, is suitable for the preparation of single crystal metal foils of various two-dimensional sizes, and has the advantages of high single crystal conversion rate, low cost and low energy consumption.
[0004] In a first aspect, the present application provides a method for preparing a single crystal metal foil, comprising: pre-treating a polycrystalline metal foil raw material to obtain a pre-treated polycrystalline metal foil; the pre-treatment comprises co-heat-treating the polycrystalline metal foil raw material with a substance containing a chalcogen element so that atoms of the chalcogen element are deposited on the surface of the polycrystalline metal foil raw material; and then annealing the pre-treated polycrystalline metal foil to obtain a single crystal metal foil.
[0005] In some embodiments of the present application, the substance containing chalcogen elements includes one or more of simple chalcogen elements, oxides of chalcogen elements, and solutions containing simple chalcogen elements.
[0006] In some embodiments of the present application, the chalcogen element includes one or more of sulfur, selenium, and tellurium.
[0007] In some embodiments of the present application, based on the total surface area of the polycrystalline metal foil raw material, the amount of the chalcogen element and / or the chalcogen element oxide is greater than or equal to 0.1 mol / cm2 .
[0008] In some embodiments of the present application, the concentration of the chalcogen element in the solution containing the chalcogen element is 0.5 mol / L-1.5 mol / L.
[0009] In some embodiments of the present application, the temperature of the co-heat treatment is 500° C.-800° C., and the time of the co-heat treatment is 0.5 h-2 h.
[0010] In some embodiments of the present application, the pretreatment is performed under a protective atmosphere.
[0011] In some embodiments of the present application, the annealing treatment includes heating the pretreated polycrystalline metal foil to 1020°C-1050°C in an atmospheric atmosphere, keeping the temperature for 5h-10h, and cooling to obtain a single crystal metal foil; the single crystal conversion rate of the single crystal metal foil is greater than or equal to 98%.
[0012] In some embodiments of the present application, the polycrystalline metal foil raw material includes polycrystalline gold foil or polycrystalline platinum foil; the purity of the polycrystalline metal foil raw material is greater than or equal to 99.985%.
[0013] In a second aspect, the present application provides a single crystal metal foil, which is prepared by the preparation method provided in the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1A This is an optical electron microscope scanning image of the single crystal gold foil prepared in Example 1;
[0015] Figure 1B This is an optical electron microscope scanning image of the gold foil prepared in Comparative Example 1;
[0016] Figure 2A This is an optical electron microscope scanning image of polycrystalline gold foil raw material;
[0017] Figure 2B This is an optical electron microscope scanning image of the single crystal gold foil prepared in Example 5;
[0018] Figure 3 This is the EBSD scanning image of the polycrystalline gold foil raw material;
[0019] Figure 4 This is the EBSD scanning image of the single crystal gold foil prepared in Example 1;
[0020] Figure 5 This is the EBSD scanning image of the single crystal gold foil prepared in Example 2;
[0021] Figure 6 This is the EBSD scanning image of the single crystal gold foil prepared in Example 3;
[0022] Figure 7This is the EBSD scanning image of the single crystal gold foil prepared in Example 4. DETAILED DESCRIPTION
[0023] The following is a clear and complete description of the technical solutions and drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available products.
[0025] Grain boundary: refers to the area where the atomic arrangement in the crystal is discontinuous. It is the interface between grains with the same structure but different orientations. It can easily become the starting point for crack propagation, thereby affecting the lattice structure of the crystal material and reducing the reliability and availability of the crystal.
[0026] Single crystal: refers to the particles inside the crystal that are regularly and periodically arranged in three-dimensional space. The lattice in the entire crystal is continuous, without grain boundaries, and therefore has anisotropy, that is, the physical properties in different directions are different. This characteristic makes it exhibit excellent performance in terms of mechanical strength, high temperature performance, etc.
[0027] Electron Backscatter Diffraction (EBSD): Use backscattered electron diffraction in a scanning electron microscope (SEM) to obtain the crystallographic information of the sample.
[0028] Chemical Vapor Deposition (CVD): The process of depositing atoms or molecules in a gas onto a solid substrate through a chemical vapor reaction under high temperature and specific atmosphere conditions. In some embodiments of the present application, both the pretreatment and the annealing treatment are performed in a CVD tube furnace.
[0029] Chalcogenide elements: elements of group 16 (VIA) in the periodic table, including sulfur (S), selenium (Se), and tellurium (Te). The present application uses substances containing chalcogenide elements as pretreatment materials for polycrystalline metal foil raw materials, which promotes the conversion of polycrystalline metal into single crystal metal.
[0030] D50 particle size: The particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, also called median particle size or median particle size.
[0031] Two-dimensional size: refers to length and width. The two-dimensional size in this scheme refers to various shapes and sizes of polycrystalline metal foil raw materials or single crystal metal foil in the plane.
[0032] Single crystal metal foil has excellent electrical and thermal conductivity, flexibility and ductility due to its own characteristics of no grain boundaries. It can be used in communications, sensors, precision electronic components and other fields to eliminate grain boundary resistance, improve mechanical properties and reduce signal loss. In addition, single crystal metal foil can also be used as a growth substrate for various two-dimensional materials, such as graphene, boron nitride, molybdenum disulfide and transition metal sulfides. At present, there are three main methods for preparing single crystal metal foil: one is to place the metal material on a high temperature resistant flat substrate, heat it to a molten state, and then solidify and reconstruct it into a single crystal metal foil on the substrate surface; the second is to press and roll the polycrystalline metal foil while annealing at high temperature, so that the polycrystalline metal surface undergoes recrystallization and obtains stress conversion into a single crystal; the third is to change the movement and arrangement of metal atoms by adjusting the placement of the polycrystalline metal foil during annealing, thereby promoting the formation of single crystals, such as "tilted placement annealing method" and "vertical placement annealing method". However, measures such as applying stress and adjusting the placement method in these methods only play a weak auxiliary role. The single crystal transformation of polycrystalline metals is mainly achieved by high-temperature annealing. The degree of single crystal transformation is limited by the shape and size of the polycrystalline metal. When the volume is large, the effect of the above auxiliary measures is even more negligible, which will lead to inconsistent overall single crystal degree of the final product, and the occurrence of local single crystal and local polycrystalline. In addition, relying solely on high temperature to prepare single crystal metal foil will consume a lot of energy and heat, and it is impossible to avoid the loss of metal materials, resulting in high preparation costs and low conversion efficiency of single crystal metals.
[0033] In view of this, the embodiment of the present application provides a single crystal metal foil and a preparation method thereof, wherein the polycrystalline metal foil raw material is pretreated before annealing, including co-heat treatment with a substance containing chalcogen elements, so that the atoms of the chalcogen elements are deposited on the surface of the polycrystalline metal foil raw material. In the subsequent annealing process, these atoms of the chalcogen elements can reduce the driving barrier required for the conversion of polycrystalline into single crystals, which can not only improve the efficiency of single crystal conversion, but also reduce the energy consumption required for annealing. This method is suitable for preparing single crystal metal foils of various two-dimensional sizes, and its conversion rate can reach 98% or more, and the single crystal has good uniformity, and has the advantages of high efficiency, low cost, and low energy consumption.
[0034] The present application provides a method for preparing a single crystal metal foil, comprising:
[0035] S101, pre-treating a polycrystalline metal foil raw material to obtain a pre-treated polycrystalline metal foil: comprising co-heat-treating the polycrystalline metal foil raw material with a substance containing a chalcogen element, so that atoms of the chalcogen element are deposited on the surface of the polycrystalline metal foil raw material;
[0036] S102, annealing the pre-treated polycrystalline metal foil obtained in step S101 to obtain a single crystal metal foil.
[0037] The preparation method adds a pretreatment step before the traditional annealing treatment, so that the atoms of the chalcogen elements are deposited on the surface of the polycrystalline metal foil raw material, especially the atoms of the chalcogen elements deposited at the polycrystalline grain boundaries, which helps to reduce the driving barrier of the polycrystalline metal to the single crystal metal, so that only a lower potential energy is needed to promote the orderly movement and arrangement of the metal atoms, thereby reducing the heat energy required for the annealing treatment to convert into a single crystal metal foil. Compared with the traditional preparation method that only relies on high-temperature annealing treatment to drive the formation of single crystals, the preparation method provided by the present application can significantly improve the single crystal conversion rate and crystal uniformity, while also reducing heat energy consumption and saving preparation time.
[0038] In the embodiment of the present application, before the pretreatment of step S101, the surface of the polycrystalline metal foil raw material is also cleaned and dried. Surface cleaning includes using a cleaning agent and water to clean the surface of the polycrystalline metal foil raw material in sequence, and the cleaning agent includes an organic solvent, such as but not limited to acetone and / or isopropanol. The organic solvent has good solubility and volatility, and can remove oil stains on the surface of the polycrystalline metal foil with less residue. Water is used to thoroughly wash away the dust and residual cleaning agent on the surface of the polycrystalline metal foil raw material. The surface cleaning method includes ultrasonic cleaning, and the time for a single ultrasonic cleaning is 10min-15min. The drying method after cleaning can be, for example, one of standing drying at room temperature and drying with nitrogen. In some specific embodiments of the present application, surface cleaning includes placing the polycrystalline metal foil raw material in acetone, isopropanol and deionized water in sequence for ultrasonic cleaning for 13-15min respectively.
[0039] In step S101, the polycrystalline metal foil raw material can be purchased from the market, including polycrystalline gold foil or polycrystalline platinum foil, and its thickness is 22μm-28μm, for example, it can be 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm. In some specific embodiments of the present application, the thickness of the polycrystalline metal foil raw material is 24μm-26μm. The polycrystalline metal foil raw material has a suitable thickness, which is conducive to ensuring a high single crystal conversion rate and saving the heat energy and annealing time required for its complete conversion into single crystals.
[0040] In the embodiment of the present application, the purity of the polycrystalline metal foil raw material is greater than or equal to 99.985%, for example, it can be but not limited to 99.985%, 99.986%, 99.987%, 99.988%, 99.989%, 99.999%. The high purity of the polycrystalline metal foil raw material can prevent impurities from interfering with the movement and arrangement of metal atoms during the annealing process, thereby hindering the formation of single crystals. In theory, the higher the purity of the polycrystalline metal foil raw material, the more conducive it is to converting it into a single crystal.
[0041] In the embodiment of the present application, the chalcogen element is selected from one or more of sulfur, selenium and tellurium.
[0042] In the embodiment of the present application, the substance containing the chalcogen element includes one or more of a simple substance of the chalcogen element, an oxide of the chalcogen element, or a solution containing the simple substance of the chalcogen element.
[0043] In some embodiments of the present application, the simple substance of the chalcogen element and the oxide of the chalcogen element may be a powder, and its D50 particle size may be 0.1 μm-0.5 μm, for example, but not limited to 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm. The simple substance of the chalcogen element and the oxide of the chalcogen element having a suitable powder particle size is conducive to controlling the speed of its gasification and deposition.
[0044] In some embodiments of the present application, the solution containing the chalcogen element can be a 98% concentrated sulfuric acid solution. Using a concentrated sulfuric acid solution as a solvent can prevent other impurities from being deposited on the surface of the polycrystalline metal foil raw material after other solutions are vaporized at high temperature, thereby adversely affecting the subsequent single crystal conversion. A high concentration of concentrated sulfuric acid solution is beneficial for fully dissolving the chalcogen element.
[0045] In some specific embodiments of the present application, the substance containing chalcogen elements may be, for example but not limited to, one of sulfur powder, selenium powder, tellurium powder, selenium dioxide powder, tellurium dioxide powder, and a concentrated sulfuric acid solution containing elemental sulfur and / or elemental selenium and / or elemental tellurium.
[0046] In the embodiment of the present application, the pretreatment is carried out under a protective atmosphere, and the protective atmosphere includes an inert gas, such as but not limited to argon and helium. The flow rate of the protective atmosphere introduced into the first heating furnace is 100sccm-200sccm, such as 100sccm, 120sccm, 140sccm, 160sccm, 180sccm, 200sccm. The inert gas atmosphere can prevent the chalcogen-containing substances from reacting with substances in the air during the pretreatment process, such as oxidation, nitridation or hydrogenation, thereby reducing the availability of the chalcogen-containing substances and slowing down the speed of chalcogen-containing atoms deposited on the surface of the polycrystalline metal foil raw material.
[0047] In the implementation manner of the present application, the pretreatment process includes heating to a first end point temperature at a first heating rate, the first end point temperature being the temperature of the co-heat treatment, the first heating rate being 15°C / min-25°C / min, for example, 15°C / min, 17°C / min, 18°C / min, 20°C / min, 22°C / min, 24°C / min, 25°C / min, and in some specific implementation manners of the present application, the first heating rate is 18°C / min-22°C / min. An appropriate heating rate can avoid the diffusion and deposition of the gas due to the instantaneous gasification of the chalcogen-containing substance, and can also reduce energy consumption.
[0048] In the embodiment of the present application, the specific process of co-heat treatment includes placing the polycrystalline metal foil raw material and the chalcogen-containing substance in a first heating furnace for heating, and the chalcogen-containing substance is vaporized or thermally decomposed under high temperature conditions, so that the chalcogen atoms in the gas are deposited on the surface of the polycrystalline metal foil raw material.
[0049] In some embodiments of the present application, the first heating furnace includes a closable furnace with its own exhaust gas treatment device, such as but not limited to a chemical vapor deposition (CVD) tube furnace or a plasma vapor deposition (PECVD) furnace.
[0050] In some embodiments of the present application, when the substance containing chalcogen elements is a single substance of chalcogen elements and / or an oxide of chalcogen elements, from the perspective of the flow direction of the protective atmosphere in the first heating furnace, the substance containing chalcogen elements is placed upstream of the polycrystalline metal foil raw material, the former is located in the upstream low temperature zone, and the latter is located in the downstream high temperature zone, and its temperature is the temperature of the co-heat treatment. In some embodiments of the present application, the temperature difference between the two temperature zones is 300℃-650℃, for example, it can be but not limited to 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃. Placing in upstream and downstream is convenient for the atoms of gaseous chalcogen elements to flow through the polycrystalline metal foil raw material with the protective atmosphere, and deposit the atoms of chalcogen elements on its surface; placing in high and low temperature zones is conducive to the continuous and uniform gasification of the substance containing chalcogen elements, avoiding the deposition rate being too fast or local deposition due to instantaneous gasification at excessively high temperatures, which makes the pretreatment effect unsatisfactory.
[0051] In some embodiments of the present application, when the chalcogen-containing substance is a simple substance of chalcogen and / or an oxide of chalcogen, it is fed into the first heating furnace in excess, and the definition of excess feeding is: after the pretreatment is completed, there is still un-vaporized chalcogen-containing substance in the low temperature zone of the first heating furnace, and these chalcogen-containing substances that have not participated in the pretreatment process can be reused in the preparation of the next single crystal metal foil. After high-temperature gasification, when the gas flows through the polycrystalline metal foil raw material, only part of the chalcogen atoms will be deposited on its surface, and the rest will be discharged from the first heating furnace with the protective atmosphere. The excessive amount of chalcogen-containing substance can be continuously gasified and deposited, ensuring that the amount of its deposition on the surface of the polycrystalline metal foil raw material is sufficient to promote the single crystal transformation during the subsequent annealing process.
[0052] In some embodiments of the present application, based on the total surface area of the polycrystalline metal foil raw material, the amount of the chalcogen element and / or the chalcogen element oxide is greater than or equal to 0.1 mol / cm 2 In some specific embodiments of the present application, when the total surface area of the polycrystalline metal foil raw material is 2 cm 2, the amount of the simple substance of the chalcogen element and / or the oxide of the chalcogen element is greater than or equal to 0.2 mol, for example, but not limited to, 0.2 mol, 0.4 mol, 0.5 mol, 0.8 mol, 1 mol.
[0053] In some other embodiments of the present application, when the substance containing chalcogen elements is a solution containing a chalcogen element, the polycrystalline metal foil raw material is immersed in it, taken out after 5min-10min, and left to dry at room temperature, at which time a film containing chalcogen elements is formed on the surface of the polycrystalline metal foil, and then the polycrystalline metal foil raw material carrying the film is placed in a first heating furnace for co-heat treatment, and the film is vaporized at high temperature to directly deposit chalcogen atoms on the surface of the polycrystalline metal foil raw material. Wherein, the concentration of the chalcogen element in the solution containing the chalcogen element is 0.5mol / L-1.5mol / L, for example, but not limited to 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.5mol / L. This concentration is conducive to ensuring the atomic content of chalcogen elements in the coating and sufficient subsequent deposition of chalcogen elements on the polycrystalline metal foil raw material. In some specific embodiments of the present application, the concentration is 0.8 mol / L-1.2 mol / L.
[0054] In the implementation manner of the present application, the temperature of the co-heat treatment is 500°C-800°C, for example, it can be but not limited to 500°C, 600°C, 700°C, 800°C. In some specific implementation manners of the present application, the temperature of the co-heat treatment is 780°C-800°C. The appropriate co-heating temperature is conducive to the continuous gasification of the chalcogen-containing substances, avoiding the instantaneous gasification due to excessive temperature, which shortens the residence time of the gas on the surface of the polycrystalline metal foil raw material, thereby affecting its deposition amount and adhesion; the co-heat treatment time is 0.5h-2h, for example, it can be but not limited to 0.5h, 1h, 1.5h, 2h. In some specific implementation manners of the present application, the co-heat treatment time is 0.9h-1.1h. The appropriate co-heating time is conducive to the atoms of the chalcogen elements having sufficient deposition amount on the surface of the polycrystalline metal foil raw material, while avoiding waste of resources. In addition, although the temperature of the co-heat treatment is not enough to make the polycrystalline metal foil raw material begin to transform into a single crystal, it can expose more polycrystalline grain boundaries. Because there are more defects at the grain boundaries and defect adsorption is more likely to occur, more chalcogen atoms are deposited at the polycrystalline grain boundaries.
[0055] In step S102, the annealing treatment includes placing the pretreated polycrystalline metal foil obtained in step S101 in a second heating furnace, heating it to an annealing temperature at a second heating rate under normal pressure and atmospheric atmosphere, keeping it at the annealing temperature, and finally cooling it to obtain a single crystal metal foil.
[0056] In the implementation manner of the present application, the second heating furnace may be, but is not limited to, an annealing furnace, an atmospheric pressure chemical vapor deposition furnace or one of the first heating furnaces described above, which will not be described in detail here.
[0057] In the implementation manner of the present application, the second heating rate is 15°C / min-25°C / min, for example, it can be 15°C / min, 18°C / min, 20°C / min, 22°C / min, 24°C / min, 25°C / min. In some specific implementation manners of the present application, the second heating rate is 18°C / min-22°C / min. A suitable heating rate during the annealing process can avoid rapid heating leading to a large amount of migration of grain boundaries and further damage to the lattice structure of the polycrystalline metal foil, which helps to increase the grain size and prepare for single crystal conversion.
[0058] In the implementation manner of the present application, the annealing temperature is 1020°C-1050°C, for example, it can be 1020°C, 1030°C, 1040°C, 1050°C; the holding time at the annealing temperature is 5h-10h, for example, it can be but not limited to 5h, 6h, 7h, 8h, 9h, 10h. In some specific implementation manners of the present application, the annealing time is 5h-6h. Appropriate annealing temperature and time give metal atoms enough free energy to make them move, and the atomic arrangement changes from a disordered state to an ordered state, thereby restoring the lattice order of the polycrystalline metal foil, repairing lattice damage and defects, and finally obtaining a single crystal metal foil with a single orientation and a smooth surface.
[0059] In step S101, the pretreatment also includes a first cooling process after the co-heat treatment. In step S102, the annealing treatment also includes a second cooling process after the heat preservation treatment. Both the first cooling process and the second cooling process are natural cooling with the furnace to avoid hardening of the single crystal metal foil due to excessive cooling. At the same time, the residual heat in the slow cooling process helps to further regularize the crystal morphology and enhance the toughness and ductility of the single crystal metal foil.
[0060] In step S101 and step S102, the first heating furnace and the second heating furnace are both placed in a negative pressure ventilation environment. Since chalcogen compounds have certain toxicity, the pretreatment and annealing treatments both involve chalcogen-containing substances and their gasification processes. Such a setting can avoid damage to operators and the environment and ensure the safety of the production process.
[0061] In the embodiment of the present application, a morphology characterization device is used to obtain the surface morphology of the single crystal metal foil finally produced. The morphology characterization device can be, for example, but not limited to, one or more of an optical electron microscope, a scanning electron microscope, a scanning tunneling microscope, and an X-ray diffraction.
[0062] In the embodiment of the present application, the single crystal metal foil finally obtained completes the process from polycrystalline (such as Figure 1A) to single crystal (such as Figure 1B ) is reconstructed, the grain boundaries disappear significantly, and the original polycrystalline domain state is transformed into a single uniform single crystal state. Relative to the polycrystalline metal foil raw material, the single crystal conversion rate is greater than or equal to 98%, for example, it can be but not limited to 98%, 98.5%, 99%, 99.5%, 99.8%, 100%.
[0063] The preparation method provided in the embodiment of the present application is suitable for preparing single crystal metal foils of various two-dimensional sizes. This is because during its pretreatment process, the polycrystalline metal foil as a whole is fully in contact with the gas formed after the chalcogen-containing substance is vaporized, and atoms of the chalcogen are randomly deposited at various locations on its surface. The deposition amount per unit area is not affected by the two-dimensional size of the polycrystalline metal foil, and it can be ensured that each part of the single crystal metal foil obtained after annealing has a uniform single crystal conversion degree.
[0064] In the prior art, the preparation of single crystal metal usually requires annealing in a reducing atmosphere, because this atmosphere helps to eliminate metal internal stress, refine grains, and improve single crystal conversion rate. The preparation method provided in this application adds a pretreatment step before annealing, that is, atoms of chalcogen elements are deposited on the surface of the polycrystalline metal foil raw material, especially at the polycrystalline grain boundaries. During the annealing treatment, the high temperature conditions give the metal atoms more free energy to make them move. At this time, the atoms of these chalcogen elements covering the grain boundaries can reduce the driving barrier for the conversion of polycrystalline into single crystals, so that the metal atoms only need to obtain lower potential energy to move freely and arrange in order. The polycrystalline begins to recrystallize in the direction of the arrangement of the metal atoms, which increases the chances of mutual fusion of the polycrystalline grain boundaries and accelerates the speed at which small grains gradually merge into large crystal domains, thereby promoting the transformation of polycrystalline metal foil into single crystal metal foil. Therefore, the annealing treatment in the preparation method provided in the embodiment of the present application does not require providing specific atmosphere conditions, and even if it is carried out in an atmospheric atmosphere, a single crystal conversion rate of 98% or above can be achieved. At the same time, the heat energy and annealing time required for the traditional preparation of single crystal metal foil are saved, thereby greatly reducing production costs.
[0065] In summary, the preparation method provided in the embodiments of the present application effectively solves the problems of high preparation cost and low single crystal conversion rate of single crystal metal foil in the prior art, and there is no loss of raw materials before and after the preparation process, and is not limited by the two-dimensional size of the polycrystalline metal foil. Annealing treatment can be completed in an atmospheric atmosphere to obtain a single crystal metal foil with a high single crystal conversion degree. It has the advantages of high efficiency, low cost, and low energy consumption, and can be widely used in industrial production.
[0066] The present application also provides a single crystal metal foil, which is prepared by the preparation method provided in the present application. The single crystal metal foil has a high degree of single crystallization, a uniform crystal phase composition, almost no grain boundaries inside, a flat and smooth surface, and excellent anisotropy, electrical and thermal conductivity, plasticity, and barrier properties.
[0067] The single crystal metal foil provided in the embodiments of the present application can be used in the fields of packaging, energy, precision electronic components, aerospace, medical equipment, etc.; it can also be used as a growth substrate for various two-dimensional materials or nanomaterials, such as graphene, boron nitride, molybdenum disulfide and other transition metal chalcogenides, etc., and can be reused many times.
[0068] The technical solution of the present application is further described below with multiple embodiments.
[0069] The polycrystalline gold foil raw material with a purity of 99.985% and a thickness of 25 μm was cut into three sizes of polycrystalline gold foil raw material: 1 cm long × 1 cm wide, 2.5 cm long × 2.5 cm wide, and 5 cm long × 2.5 cm wide.
[0070] Example 1
[0071] (1) Cleaning and drying: A 1 cm long × 1 cm wide polycrystalline gold foil raw material was placed in acetone, isopropanol, and deionized water for ultrasonic cleaning for 15 min respectively, and then allowed to stand and dry;
[0072] (2) Pretreatment: The cleaned and dried polycrystalline gold foil raw material is placed in the central quartz boat (downstream high temperature zone) of the CVD tube furnace, and 0.5 mol of selenium powder is placed in the low temperature zone upstream of the polycrystalline gold foil raw material. The temperature difference between the two temperature zones is 550°C. The cover of the CVD tube furnace is closed, and 200 sccm of argon gas is continuously introduced into it. The temperature of the downstream high temperature zone is increased to 800°C at a first heating rate of 20°C / min. After heating for 1 hour, the power of the CVD tube furnace is turned off, and the cover is opened to cool it and then taken out to obtain the pretreated polycrystalline gold foil;
[0073] (3) Annealing treatment: Place the pretreated polycrystalline gold foil in a CVD tube furnace, maintain the atmospheric atmosphere, and heat it to 1050°C at a second heating rate of 20°C / min. After keeping the temperature for 5 hours, turn off the power of the CVD tube furnace, open the cover, wait for it to cool, and then take it out to obtain a single crystal gold foil.
[0074] Example 2
[0075] The only difference from Example 1 is that sulfur powder is used in the pretreatment step, and the temperature difference between the upstream low-temperature zone where the sulfur powder is located and the downstream high-temperature zone where the polycrystalline gold foil raw material is located is 620°C.
[0076] Example 3
[0077] The only difference from Example 1 is that tellurium powder is used in the pretreatment step, and the temperature difference between the upstream low-temperature zone where the tellurium powder is located and the downstream high-temperature zone where the polycrystalline gold foil raw material is located is 300°C.
[0078] Example 4
[0079] The only difference from Example 1 is that tellurium dioxide powder is used in the pretreatment step, and the temperature difference between the upstream low-temperature zone where the tellurium dioxide powder is located and the downstream high-temperature zone where the polycrystalline gold foil raw material is located is 300°C.
[0080] Example 5
[0081] (1) Cleaning and drying: the same as in Example 1;
[0082] (2) Pretreatment: The cleaned and dried polycrystalline gold foil raw material is immersed in 98% concentrated sulfuric acid with a selenium concentration of 1 mol / L. After soaking for 5 minutes, the polycrystalline gold foil raw material is taken out and left to dry. The polycrystalline gold foil raw material is then placed in the central quartz boat of a CVD tube furnace. The cover of the CVD tube furnace is closed, and 200 sccm of argon gas is continuously introduced into the boat. The temperature is increased to 800°C at a first heating rate of 20°C / min. After heating for 1 hour, the power of the CVD tube furnace is turned off, the cover is opened, and the polycrystalline gold foil is taken out after cooling to obtain the pretreated polycrystalline gold foil.
[0083] (3) Annealing treatment: The only difference from Example 1 is that the final temperature of the heating is 1020°C.
[0084] Comparative Example 1
[0085] The only difference from Example 1 is that no selenium powder is added in the pretreatment step.
[0086] The single crystal gold foil prepared in Example 1 and the gold foil prepared in Comparative Example 1 were characterized by an optical electron microscope, with a scale length of 500 μm. Figure 1A and Figure 1B ;
[0087] The polycrystalline gold foil raw material and the single crystal gold foil prepared in Example 5 were characterized by an optical electron microscope, with a scale length of 100 μm. Figure 2A and Figure 2B ;
[0088] The EBSD characterization was performed on the polycrystalline gold foil raw material and the single crystal gold foil prepared in the above Examples 1-4 using a scanning electron microscope. The scale length was 0.5 mm. The scanned images were shown in FIG. Figure 3-Figure 7 , the crystal phase composition results are shown in Table 1:
[0089] Table 1 Crystalline phase composition of Examples 1-5 and Comparative Example 1
[0090] serial number Crystalline phase composition Polycrystalline gold foil raw material polyphase Example 1 Single Phase Example 2 Single Phase Example 3 Single Phase Example 4 Single Phase Example 5 Single Phase Comparative Example 1 polyphase
[0091] Figure 1A This is an optical electron microscope scanning image of the single crystal gold foil prepared in Example 1. Figure 1B This is an optical electron microscope scanning image of the gold foil prepared in Comparative Example 1. Figure 1Aand Figure 1B It can be seen that Example 1 achieves complete transformation from polycrystalline to single crystal, while the gold foil of Comparative Example 1 is still in a polycrystalline state, and its microstructure has obvious grain boundaries. The only difference between Comparative Example 1 and Example 1 is that the polycrystalline metal foil raw material is not pretreated, which shows that the pretreatment step in the preparation method provided by the present application plays an important role in promoting the degree of transformation of polycrystalline gold foil to single crystal gold foil.
[0092] Figure 2A This is an optical electron microscope scanning image of polycrystalline gold foil raw material; Figure 2B This is an optical electron microscope scanning image of the single crystal gold foil prepared in Example 5; Figure 3 This is the EBSD scanning image of the polycrystalline gold foil raw material; Figure 4 This is the EBSD scanning image of the single crystal gold foil prepared in Example 1; Figure 5 This is the EBSD scanning image of the single crystal gold foil prepared in Example 2; Figure 6 This is the EBSD scanning image of the single crystal gold foil prepared in Example 3; Figure 7 This is the EBSD scanning image of the single crystal gold foil prepared in Example 4. Figure 2A and Figure 3 It can be seen that the polycrystalline gold foil raw material has obvious polycrystalline grain boundaries and polycrystalline composition. After the single-crystal gold foil of Examples 1-5 is pre-heated with a chalcogen element, an oxide of a chalcogen element or a solution containing a chalcogen element, and then annealed, it has a uniform crystal phase and no grain boundaries in its microstructure, indicating that Examples 1-5 have achieved complete transformation of polycrystalline gold foil into single-crystal gold foil, and the single-crystal conversion rate is as high as 100%.
[0093] In addition, the preparation steps of Examples 1-5 and Comparative Example 1 were repeated using polycrystalline gold foil raw materials of 2.5 cm long × 2.5 cm wide and 5 cm long × 2.5 cm wide. The single crystal gold foil finally obtained had almost the same degree of single crystal conversion as the single crystal gold foil of 1 cm long × 1 cm wide, proving that the preparation method provided in the present application is suitable for preparing single crystal gold foils of various two-dimensional sizes, and its single crystal conversion rate is extremely high and the effect is stable.
[0094] In summary, the preparation method provided by the present application pre-treats the polycrystalline metal foil raw material, and co-heat treats it with a substance containing chalcogen elements, so that atoms of chalcogen elements are deposited on its surface, especially at each grain boundary of the polycrystalline. These atoms of chalcogen elements help the movement and orderly arrangement of metal atoms under the high temperature conditions of annealing treatment, which can significantly improve the single crystal conversion effect of subsequent annealing treatment, and is suitable for preparing single crystal metal foils of various two-dimensional sizes. The single crystal conversion degree is extremely high and the effect is stable. The annealing treatment only needs to be carried out under normal pressure and atmospheric atmosphere, which is of great significance for saving production time and reducing energy consumption, and can be used for industrial production. The single crystal metal foil prepared by this method has almost no grain boundaries inside, and has excellent electrical and mechanical properties, and has broad application prospects in the fields of electronics, plasma, batteries, medical equipment, aerospace, etc.
[0095] The above disclosure is only the preferred embodiment of the present application, and cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and making equivalent changes according to the claims of the present invention still fall within the scope covered by the present invention.
Claims
1. A method for preparing a single crystal metal foil, characterized in that: include: Pre-treating the polycrystalline metal foil raw material to obtain pre-treated polycrystalline metal foil; The pretreatment includes co-heat treating the polycrystalline metal foil raw material with a substance containing a chalcogen element, so that atoms of the chalcogen element are deposited on the surface of the polycrystalline metal foil raw material; The pretreated polycrystalline metal foil is then annealed to obtain a single crystal metal foil.
2. The method for preparing a single crystal metal foil according to claim 1, characterized in that: The chalcogen element-containing substance includes one or more of a simple substance of the chalcogen element, an oxide of the chalcogen element, and a solution containing the simple substance of the chalcogen element.
3. The method for preparing a single crystal metal foil according to claim 1 or 2, characterized in that: The chalcogenide elements include one or more of sulfur, selenium and tellurium.
4. The method for preparing a single crystal metal foil according to claim 2, characterized in that: Based on the total surface area of the polycrystalline metal foil raw material, the amount of the chalcogen element and / or the chalcogen element oxide is greater than or equal to 0.1 mol / cm 2 .
5. The method for preparing a single crystal metal foil according to claim 2, characterized in that: The concentration of the chalcogen element in the solution containing the chalcogen element is 0.5 mol / L-1.5 mol / L.
6. The method for preparing a single crystal metal foil according to claim 1, characterized in that: The temperature of the co-heat treatment is 500° C.-800° C., and the time of the co-heat treatment is 0.5 h-2 h.
7. The method for preparing a single crystal metal foil according to claim 1, characterized in that: The pretreatment is carried out under a protective atmosphere.
8. The method for preparing a single crystal metal foil according to claim 1, characterized in that: The annealing treatment includes heating the pretreated polycrystalline metal foil to 1020° C.-1050° C. in an atmospheric atmosphere, keeping the temperature for 5 h-10 h, and cooling to obtain the single crystal metal foil; the single crystal conversion rate of the single crystal metal foil is greater than or equal to 98%.
9. The method for preparing a single crystal metal foil according to claim 1, characterized in that: The polycrystalline metal foil raw material includes polycrystalline gold foil or polycrystalline platinum foil; the purity of the polycrystalline metal foil raw material is greater than or equal to 99.985%.
10. A single crystal metal foil prepared by the preparation method according to any one of claims 1 to 9.